Management of stable angina. Issue 932 (1st June 2003) - Jain, A; Wadehra, V; Timmis, A D
Abstract : Ischaemic heart disease may present as a wide variety of clinical entities including unstable or stable angina pectoris, acute myocardial infarction, and occasionally heart failure. Chronic stable angina is a common condition and results in a considerable burden for both the individual and society. The goals in management are (i) treatment of other conditions that may worsen angina; (ii) modification of risk factors and treatment with medications for coronary artery disease to improve outcome; and (iii) effective relief of anginal symptoms. There are limitations to the methods available to risk-stratify patients, and the optimal treatment strategy remains unclear. The benefits of lifestyle modification cannot be over-emphasised, and appropriate attention to modifiable risk factors is paramount. The mortality benefit of lipid lowering treatment and antiplatelet therapy is well proved. However the evidence base for anti-ischaemic therapy is less rigorous, being based mainly on extrapolations from studies of acute coronary syndromes. Angioplasty has been shown to be more effective in relief of symptoms than medical therapy alone, but provides no mortality benefit. Coronary artery bypass surgery, however, has been shown to reduce mortality in patients with severe proximal coronary disease when compared with medical management alone.